Development of E-LKPD Based on Problem Based Learning on Excretory System Material for High Schools - Angga Bagas Saputra; Afreni Hamidah; Raissa Mataniari (Postgraduate, University of Mataram, 2024)
Learning carried out using learning tools in the form of printed LKPD makes students easily bored. Lack of use of technology in learning also often makes students less motivated. Therefore, this research aims to develop more innovative learning tools and see their feasibility which will be validated by media experts and material experts. The product developed is a PBL-based E-LKPD on excretory system material. This research was carried out at the Madrasah Aliyah Laboratory in Jambi City. This research is development research (R&D) with the ADDIE development model. Data collection techniques use observation, interviews and documentation. The instruments used were questionnaires and teacher assessment sheets. The trial was carried out on 6 students and 15 students. Material validation was 87.5% in the